“I was afraid they will be judging me and even deny me the service”: Experiences of denial and dissuasion during abortion care in Ethiopia - Bercu, Chiara; Jacobson, Laura E.; Gebrehanna, Ewenat; Ramirez, Ana Maria; Katz, Anna J.; Filippa, Sofía; Baum, Sarah E. (Frontiers in Global Women's Health, 2022)
Introduction Disrespect and abuse are components of poor quality abortion care. This analysis aimed to understand negative experiences of care from perspectives of abortion clients in public and private facilities in Ethiopia. Study Design We conducted 23 in-depth interviews with people who obtained abortion care in Addis Ababa, Ethiopia as well as Aksum and Mekele in Tigray State, Ethiopia. The interviews were coded using a priori and emergent codes and we conducted thematic analysis to understand negative interactions with providers from participant's perspectives. Results Participants experienced denial of abortion services along their pathway to care and attempts by providers to dissuade them prior to providing an abortion. Underlying both the denial and the dissuasion were reports of disrespect and condemnation from providers. Participants described how providers doubted or forced them to justify their reasons for having an abortion, stigmatized them for seeking multiple abortions or later abortions, and ascribed misinformation about abortion safety. Despite reports of denial, dissuasion, and disrespect, abortion clients generally felt that providers had their best interest at heart and were grateful for having access to an abortion. Conclusions Participants in Ethiopia experienced providers as gatekeepers to legal abortion services, facing disrespect and judgment at facilities where they sought care. Interventions aimed at increasing awareness of abortion laws such that clients understand their rights and values clarification interventions for providers could help reduce barriers to accessing care and improve the quality of abortion services.